Mining Long Patterns - ZHU, Feida (Institutional Knowledge at Singapore Management University, 2014)
The value and importance of long patterns are gaining increasing recognition in a wide range of domains including bioinformatics, social network analysis, software engineering and business intelligence. Yet the task of mining long patterns has remained a challenge due to the prohibitively large number of smaller patterns which often need to be generated first. In this chapter, we first use a pattern lattice model to illustrate and compare various mining paradigms. Then we present recent studies for mining long patterns according to their respective pattern mining paradigms. For each category, we discuss the representative algorithms and the state-of-the-art development.